Evaluating four measures of water quality in clay pots and plastic safe storage containers in Kenya. (1st November 2016) - Murphy, Jennifer L.; Ayers, Tracy L.; Knee, Jacqueline; Oremo, Jared; Odhiambo, Aloyce; Faith, Sitnah H.; Nyagol, Ronald O.; Stauber, Christine E.; Lantagne, Daniele S.; Quick, Robert E.
Abstract: Household water treatment with chlorine can improve microbiological quality and reduce diarrhea. Chlorination is typically assessed using free chlorine residual (FCR), with a lower acceptable limit of 0.2 mg/L, however, accurate measurement of FCR is challenging with turbid water. To compare potential measures of adherence to treatment and water quality, we chlorinated recently-collected water in rural Kenyan households and measured total chlorine residual (TCR), FCR, oxidation reduction potential (ORP), and E. coli concentration over 72 h in clay and plastic containers. Results showed that 1) ORP served as a useful proxy for chlorination in plastic containers up to 24 h; 2) most stored water samples disinfected by chlorination remained significantly less contaminated than source water for up to 72 h, even in the absence of FCR; 3) TCR may be a useful proxy indicator of microbiologic water quality because it confirms previous chlorination and is associated with a lower risk of E. coli contamination compared to untreated source water; and 4) chlorination is more effective in plastic than clay containers presumably because of lower chlorine demand in plastic. Highlights: ORP served as a useful proxy for chlorination in plastic containers up to 24 h. E. coli in chlorinated water stayed low up to 72 h even as free chlorine decreased. Total chlorine persisted longer than free chlorine in treated, stored water. Plastic containers had higher chlorine and lower E. coli levels over 72 h than clay.